2018
DOI: 10.1021/acs.jpcc.8b08448
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Color of Maya Blue: Reexamination of Literature Data Based On the Dehydroindigo Model

Abstract: An analysis of literature data studying the composition and color of Maya blue (MB) type materials prepared from indigo, dehydroindigo, and different aluminosilicates, accompanied by new spectral data, is presented. After thermal treatment at above 100 °C, indigo-based specimens displayed Raman and UV−vis spectroscopic features common to those of equivalent dehydroindigo-based replicants, thus supporting the socalled dehydroindigo model (J. Phys. Chem. B 2006, 110, 6027−6039) in which the dehydroindigo/indigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…This was later addressed by Domenech et al in 2013 [134], whose main findings pointed to the presence of dehydroindigo, another yellow derivative of indigo. Recently, the same group revisited the subject and discussed evidence that supports their previous results [135].…”
Section: Results Of Colors Characterizationmentioning
confidence: 84%
“…This was later addressed by Domenech et al in 2013 [134], whose main findings pointed to the presence of dehydroindigo, another yellow derivative of indigo. Recently, the same group revisited the subject and discussed evidence that supports their previous results [135].…”
Section: Results Of Colors Characterizationmentioning
confidence: 84%
“…According to the literature [22,37,38], the Maya blue pigment can be produced (i) by adding the dye from a solution (containing indoxylacetate or indigo by vat-dying) to the clays (palygorskite or sepiolite) or (ii) by mixing the powdered components and heating the mixture. It is generally reported that 1 wt% is the "optimum" amount of indigo used to prepare genuine Maya blue pigment [32]. However, in our study we have also synthesized laboratory mock-ups including a wider range of indigo loadings (specifically 0.3 and 5 wt%) to evaluate the sensitivity and defining the spectral markers and colorimetric properties for Maya blue on models with the aim of interpreting non-invasive in situ results.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, (a) according to the model proposed by Doménech et al various indigoid molecules, besides indigo, are reported to coexist in the clay matrix-externally bound or internally incorporated in the channels-and among them dehydroindigo is favored by the increase of temperature [25,32,59,60].…”
Section: The Discrimination Among Indigo and Maya-bluesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only in modern times it was found that the enormous stability and peculiar hue of the pigment result from the intercalation of indigo molecules into the channel structure of the clay mineral palygorskite (Appendix A), which predominated in the mud. The location of the dye molecules on the clay support, as well as the origin and variability of the colour, are still not fully understood, although they have been studied extensively since the 1960s [8][9][10][11]. In any case, this is one of the very first examples of targeted intercalation of clays by organic molecules in order to get hybrid materials-organoclays with new useful properties [12], such as stable colour which persists even at high temperatures and in an aggressive chemical environment [13].…”
Section: Earths and Ochres-a Brief Overviewmentioning
confidence: 99%